2018
DOI: 10.1111/cen.13905
|View full text |Cite
|
Sign up to set email alerts
|

Higher circulating androgens and higher physical activity levels are associated with less central adiposity and lower risk of cardiovascular death in older men

Abstract: Objective Low endogenous sex hormones and low physical activity (PA) levels have been associated with CVD risk. Whether these interact to influence CVD outcomes remains unclear. We assessed whether sex hormone concentrations and PA were additively associated with lower central adiposity and CVD risk. Patients 3351 community‐dwelling men, mean age 77 years. Measurements Baseline testosterone (T), dihydrotestosterone (DHT) and oestradiol (E2) were assayed. Levels of PA were ascertained by questionnaire. Men were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
2
9
0
Order By: Relevance
“…68 Higher circulating androgens and physical activity were linked to lower central adiposity at baseline and fewer CVD deaths in the recent follow-up study. 69 A potential synergic effect of androgens and physical activity on cardiometabolic outcomes in aging males is consistent with previous data. 69 Males with both hypogonadism and moderate-to-severe lower urinary tract symptoms possess a more severe cardiometabolic risk profile and benefit more from T treatment than males with mild lower urinary tract symptoms.…”
Section: Androgens In Cmssupporting
confidence: 90%
See 1 more Smart Citation
“…68 Higher circulating androgens and physical activity were linked to lower central adiposity at baseline and fewer CVD deaths in the recent follow-up study. 69 A potential synergic effect of androgens and physical activity on cardiometabolic outcomes in aging males is consistent with previous data. 69 Males with both hypogonadism and moderate-to-severe lower urinary tract symptoms possess a more severe cardiometabolic risk profile and benefit more from T treatment than males with mild lower urinary tract symptoms.…”
Section: Androgens In Cmssupporting
confidence: 90%
“…69 A potential synergic effect of androgens and physical activity on cardiometabolic outcomes in aging males is consistent with previous data. 69 Males with both hypogonadism and moderate-to-severe lower urinary tract symptoms possess a more severe cardiometabolic risk profile and benefit more from T treatment than males with mild lower urinary tract symptoms. 70 T therapy is a highly effective treatment for ameliorating lower urinary tract symptoms in hypogonadal men.…”
Section: Androgens In Cmssupporting
confidence: 90%
“…Previous studies have demonstrated that low testosterone levels can lead to an increased risk of cardiovascular disease ( 60 62 ). Dihydrotestosterone is an important hemostatic steroid with inhibitory effects on platelets ( 63 ). Dihydrotestosterone cannot be converted to estrogen by aromatase, but a previous study has indicated that testosterone can be converted to estradiol and act through estrogen receptors ( 64 ).…”
Section: Discussionmentioning
confidence: 99%
“…49 A prospective study of 3351 community-dwelling men showed that men with low T had higher BMI, WC, and risk of metabolic syndrome (MetS) after a 10-year follow-up. 50 Interestingly, men with higher baseline T levels not only had the lowest BMI, WC, and risk of MetS, but they also had the lowest risk of incident CVD Caliber and Saad; Androgens: Clinical Research and Therapeutics, 1.1 http://online.liebertpub.com/doi/10.1089/andro.2020.0010 events-irrespective of physical activity level-and had the lowest risk of dying from CVD. 50 Low T is a particularly strong predictor of the development of central adiposity 51 with visceral fat accumulation.…”
Section: Bidirectional Link Between Obesity and Tdmentioning
confidence: 95%
“…50 Interestingly, men with higher baseline T levels not only had the lowest BMI, WC, and risk of MetS, but they also had the lowest risk of incident CVD Caliber and Saad; Androgens: Clinical Research and Therapeutics, 1.1 http://online.liebertpub.com/doi/10.1089/andro.2020.0010 events-irrespective of physical activity level-and had the lowest risk of dying from CVD. 50 Low T is a particularly strong predictor of the development of central adiposity 51 with visceral fat accumulation. 52 Another prospective study specifically examined the association between baseline T levels and visceral fat accumulation (measured by computed tomography) after a follow-up of 7.5 years.…”
Section: Bidirectional Link Between Obesity and Tdmentioning
confidence: 95%